The experience of conflicts (internal and external) and the sense of meaning in life. An existential approach - Rumianowska, Agnieszka (Forum Pedagogiczne, 2022)
Although there is a relatively long tradition of research into the mechanisms underlying conflicts (both internal and interpersonal ones), the existential perspective of conflict has not as yet been the subject of extensive psychological studies. From the standpoint of existential psychology, conflict is primarily an expression of an individual’s confrontation with objective existential facts: freedom and the responsibility for oneself that freedom entails, the finitude of human life, existential loneliness and fate in its broadest sense. Although conflict, so defined, is essentially an immanent feature of human existence, it becomes a problem when a strong sense of helplessness and anxiety starts to accompany it, as a person loses their purpose in life and fails to realize their personal values. This research aimed to answer the question of whether there is a relationship between an individual’s behavior in response to (internal and interpersonal) conflict and his/her sense of meaning in life and preferred values. The study covered a group of 153 students aged from 19 to 26 years. Purpose-of-life was measured using the test developed by Crumbaugh and Maholick (1964). The Schwartz Portrait Values questionnaire was used to assess the respondents’ preferences for fundamental values. The behavior of the subjects in response to conflict was examined using linguistic (frequency) analysis of the verbs used in their open-ended answers.